1991
DOI: 10.1177/001872089103300408
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of Synthetic Speech Produced by Rule: Word Monitoring and Sentence-by-Sentence Listening Times

Abstract: Previous comprehension studies using postperceptual memory tests have often reported negligible differences in performance between natural speech and several kinds of synthetic speech produced by rule, despite large differences in segmental intelligibility. The present experiments investigated the comprehension of natural and synthetic speech using two different on-line tasks: word monitoring and sentence-by-sentence listening. On-line task performance was slower and less accurate for passages of synthetic spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 29 publications
5
29
0
1
Order By: Relevance
“…In another comprehension study, we used a self-paced listening task to measure the amount of processing time subjects need to understand individual sentences in a passage of connected speech [RPLGM91]. As expected, we found that listeners 43.…”
Section: Perception Of Synthetic Speech 549supporting
confidence: 63%
“…In another comprehension study, we used a self-paced listening task to measure the amount of processing time subjects need to understand individual sentences in a passage of connected speech [RPLGM91]. As expected, we found that listeners 43.…”
Section: Perception Of Synthetic Speech 549supporting
confidence: 63%
“…Expert speech synthesizer users also have higher transcription accuracy than non-expert users (Stent et al, 2011), though research has also suggested that synthetic speech has lower comprehension rates that is attributable in part to the greater encoding demands of synthetic speech (Ralston et al, 1991). A Chi-square test yielded a significant difference at p < .05 on this measure, as can be seen in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic speech has also been found to take longer to process than natural speech, even in cases in which comprehension is equivalent (Ralston, Pisoni, Lively, & Greene, 1991). Hence, another factor affecting intelligibility is the rate at which speech is presented (Higginbotham, Drazek, Kowarsky, Scally, & Segal, 1994;Reynolds & Givens, 2001;Slowiaczek & Nusbaum, 1985).…”
Section: Age Differences In Identifying Words In Synthetic Speechmentioning
confidence: 99%